FAKTOR-FAKTOR YANG MEMPENGARUHI LAMBANNYA PROSES PEMILIHAN RAJA DI NEGERI TIAL KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Juniyanti Tuarita; Nensy Lusida (Jurnal Administrasi Terapan, 2022)
The study entitled "Factors Affecting the Slow Process of the King's Election in the Tial Country of Salahutu Subdistrict Central Maluku Regency". The problems to be solved in this study are What Are the Factors Affecting the Slow Process of the King's Election in the Tial Country of Salahutu, Central Maluku Regency? The objectives of this study can be stated as follows: a. As material for information to be used as a reference for further research. b. Adding to public (academic) discourse for the development of Government Science, which deals with factors that influence the slow pace of the King's election process in Tial Country, Salahutu District, Central Maluku Regency. c. As a reference material and contribution of thought to the community in analyzing the analysis of factors that influence the slow process of the King's election in the State of Tial Country of Salahutu, Central Maluku Regency. d. As one of the requirements in the Government Science Study Program, Faculty of Social and Political Sciences, Pattimura University for the sake of obtaining a bachelor's degree in Government Science. To operationalize the variables studied in this study are measured using indicators. 1. The role of saniri in resolving dissent between soa parentah. 2. District / District Government Mediation regarding resolution of the King's Election. 3. Performance Evaluation of Actors from the District Government. With interview instruments, data and information are collected from informants. With descriptive qualitative analysis techniques the following conclusions can be obtained: 1. Saniri Negeri has played a role in resolving dissent regarding the Parentah Matarumah. But it has not been maximized because there are several obstacles, namely the absence of Saniri's body rules. Mediation from District and District Governments is very much needed in an effort to resolve the Election of the King. Such mediation is carried out by the House of Representatives Commission A Division of Government which seeks to carry out socialization regarding the position of the Saniri Negeri Agency and the Definitive Government Appointment Process. 3. The Acting Government of Tial District has not been able to carry out his duties properly to give birth to the Definitive King. Keywords: Acting Performance